The Lieb and Nazarov Inequalities for Quaternion Linear Canonical S-Transform - Danang, Dahnial; Bahri, Mawardi; Bachtiar, Nasrullah; Toaha, Syamsuddin (Journal of the Indonesian Mathematical Society, 2026)
This research introduces the quaternion linear canonical S-transform. This transform is an extension of the linear canonical S-transform within quaternion algebra. We recall the properties and present the natural link between the quaternion linear canonical transform and the quaternion linear canonical S-transform. We exploit these properties and relation to establish the Lieb and Nazarov inequalities to the quaternion linear canonical S-transform.